Effect of functional enzyme additives on the sensory and shelf-life properties of ready-to-eat breakfast cereals - Daniels, Gaynor Adele (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScFoodSc)--Stellenbosch University, 2019.